Ask Question
11 June, 09:39

Distribute. - 3 (-2x - 1)

+2
Answers (2)
  1. 11 June, 11:06
    0
    6x+3

    Step-by-step explanation:

    = (-3) (-2x + - 1)

    = (-3) (-2x) + (-3) (-1)

    = (-3) (-2x) + (-3) (-1)

    = 6x=3

    So therefore, that is how you found your answer: 6x+3
  2. 11 June, 11:19
    0
    I believe the answer should be 6x+3
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Distribute. - 3 (-2x - 1) ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers